1999
DOI: 10.1002/(sici)1099-0739(199904)13:4<279::aid-aoc843>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of H8Si8O12 with a chromium oxide surface: a model for stainless steel surface modification

Abstract: Many metal alloys are susceptible to corrosion, particularly after processing steps such as welding. Chemical vapor deposition (CVD) is an effective way to modify metal surfaces and impart specific physical and chemical properties. A hydrophobic, nanosegmented silicon oxide coating derived from the discrete cluster molecule H8Si8O12 has been shown to chemisorb to 302 and 304 stainless steel. To understand better how this cluster binds to steel, a comprehensive study of these clusters adsorbed on chromium oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…All dosing was done by backfilling the chamber to the desired pressure through a sapphire leak valve, not by line-of-sight. Separate experiments have shown that these clusters can chemisorb to stainless steel; hence, it was necessary to “condition” the chamber with an extended cluster exposure after each bake, typically a few hours. This conditioning, however, did not affect the ultimate base pressure of the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…All dosing was done by backfilling the chamber to the desired pressure through a sapphire leak valve, not by line-of-sight. Separate experiments have shown that these clusters can chemisorb to stainless steel; hence, it was necessary to “condition” the chamber with an extended cluster exposure after each bake, typically a few hours. This conditioning, however, did not affect the ultimate base pressure of the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…17 In optics, they have a fruitful area of applicability as liquid crystals. 18 They have also been proposed as possible NLO species due to their high transparency, 19 as models for oxosurfaces in micro- 20 and mesoporous silica, 21 and as metal surface and cluster additives for silicon, 22 iron, 23 and gold. 24 The cage-like molecular structure of POSS makes them potentially useful substances for separating mixtures of gases as has been observed in siloxanes 25 and silicon-based capillary membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Upon closer inspection, spectrum B bears a stronger resemblance to the valence band spectrum of an amorphous hydrogen-containing siloxane layer (SiOH x ) obtained by thermally decomposing a chemisorbed layer of H 8 Si 8 O 12 (via heating to 900 K) on Si(100)-2 × 1 (Figure 4E) than to a chemisorbed and/or physisorbed layer of H 8 Si 8 O 12 on Si(100)-2 × 1 (Figure 4C and 4D, respectively). 60,61 Due to this similarity, and the absence of five identifiable features corresponding to the Si-H and Si-O bonding molecular orbitals previously obtained for chemisorbed and physisorbed layers of H 8 Si 8 O 12 on Si(100)-2 × 1, the valence band data strongly support a reaction pathway involving cluster decomposition on the Si(111)-7 × 7 surface. The signal-to-noise ratio obtained for the valence band spectrum is considerably worse than that obtained from H 8 Si 8 O 12 chemisorbed on Si(100)-2 × 1 for a similar number of scans.…”
Section: Resultsmentioning
confidence: 64%
“…The valence band spectrum of an unreacted, condensed layer of H 8 Si 8 O 12 on a hydrogen-terminated Si(100) surface at 133 K displays five readily discernible features corresponding to the Si-H and Si-O bonding molecular orbitals (Figure 4D). 60,61 The absence of such features in the valence band spectrum of the thin oxide film derived from exposure of H 8 Si 8 O 12 to Si(111)-7 × 7 suggests the cluster cages substantially decompose following reaction with the surface. Upon closer inspection, spectrum B bears a stronger resemblance to the valence band spectrum of an amorphous hydrogen-containing siloxane layer (SiOH x ) obtained by thermally decomposing a chemisorbed layer of H 8 Si 8 O 12 (via heating to 900 K) on Si(100)-2 × 1 (Figure 4E) than to a chemisorbed and/or physisorbed layer of H 8 Si 8 O 12 on Si(100)-2 × 1 (Figure 4C and 4D, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation